2016
DOI: 10.1002/ceat.201600394
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Pretreatment of Lignocellulosic Biomass: An Effective and Environmentally Friendly Approach to Enhance Biofuel Production

Abstract: Hot water pretreatment without usage of chemicals is a particularly attractive approach for pretreatment of lignocellulosic biomass due to its fewer safety and environmental concerns as well as relatively low cost. However, a prohibitive amount of sugar degradation products limits the efficiency of such pretreatment, and excessive water consumption accompanied with the over-diluted sugar streams still impedes the implementation of this pretreatment to be an economically viable pathway. These limitations are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 97 publications
(135 reference statements)
1
33
0
Order By: Relevance
“…Apart from aromatic compounds, 18.7% HMF selectivity was obtained at a flow rate of 10 mL/min, indicating that the precursor of HMF, i.e., glucose, was susceptible to dehydration if exposed in hot water for a relative long retention time because of the lower flow rate. This corresponds with previous studies (Yan et al 2016a), which reported that glucose degraded rapidly once hydrolyzed from cellulose in hot water conditions. …”
Section: Impact Of Flow Rate On Product Distributionsupporting
confidence: 62%
See 2 more Smart Citations
“…Apart from aromatic compounds, 18.7% HMF selectivity was obtained at a flow rate of 10 mL/min, indicating that the precursor of HMF, i.e., glucose, was susceptible to dehydration if exposed in hot water for a relative long retention time because of the lower flow rate. This corresponds with previous studies (Yan et al 2016a), which reported that glucose degraded rapidly once hydrolyzed from cellulose in hot water conditions. …”
Section: Impact Of Flow Rate On Product Distributionsupporting
confidence: 62%
“…AHWF benefits from the acidic characteristic of water because of its dissociation into hydronium ions at high temperatures (e.g., 240 °C), which enhances the degradation of lignocellulosic biomass into sugar and non-carbohydrate compounds (Yan et al 2016a). To evaluate the impact of acidity on the selectivity of non-carbohydrate products, 0.05% (w/w) and 0.1% (w/w) H2SO4 were added into the hot water flowthrough system.…”
Section: Impact Of System Acidity On Product Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercalation of hemicelluloses into cellulose microfibrils and their interlinkage with lignin is another important factor for such recalcitrance (Bond et al, 2013;Yang et al, 2011). Thus, aside from loosening up the structural rigidity of celluloses and breaking up the lignin shield, the removal of hemicelluloses from the lignocellulosic matrix forms an essential part of biomass pretreatment for enhanced cellulose digestibility (Yan et al, 2016;Hayashi and Kaida, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions close to the critical point, water has several interesting properties. Among them are low viscosity and high solubility of organic substances, close to those in organic solvents, which make subcritical water an excellent medium for homogenous, rapid, and efficient reactions , , . Water in the critical region is still as polar as acetone .…”
Section: Introductionmentioning
confidence: 99%